Evaluation of antimicrobial activity of Artocarpus altilis on pathogenic microorganisms - Kamal, Tara; Muzammil, Ahmad; Omar, Muhammad Nor (Academic Information Press, 2012)
The study was aimed to evaluate the antimicrobial, MIC and MBC/MFC activities of Artocarpus altilis (twigs). In vitro antimicrobial activity was evaluated against six pathogenic microorganisms (two gram positive strains: Staphylococcus aureus (ATCC-25923) and Bacillus cereus (ATCC-11778), the Gram negative strains Escherichia coli (ATCC- 35218) and Pseudomonas aeruginosa (ATCC -27853), and two fungal strains: Candida albicans (ATCC -10231) and Cryptococcus neoformans (ATCC- 90112)) using the disc diffusion method at 2mg/disc by indicating the presence of the clear inhibition zones around each disc compared with the positive control (Streptomycin and Nystatin), while the MIC and MBC/MFC were ranged from (250-1000μg/ml) assayed by using the 96 well plates. The dried twigs of A. altilis were extracted by using the Soxhlet apparatus. The extracts of hexane and DCM were observed a moderate antimicrobial activity at (14.6±0.2mm) against Bacillus cereus, whereas 11.8±0.3mm and 11.5±0.2mm values for C. albicans respectively. The least MIC of 250μg/ml was obtained by DCM extract against S. aureus for bacteria and C. albicans and C. neoformans for fungus respectively. The results suggested that Artocarpus altilis extracts have promising therapeutic potential against bacteria and fungi.